FOREIGN POLICY AND BILATERAL COOPERATION RELATIONS OF THE REPUBLIC OF UZBEKISTAN - Mirzoumid Khamdamov; Alieva Perizat Tazabay kizi (Bright Mind Publishing, 2025)
This article is devoted to the new foreign policy of the Republic of Uzbekistan, which examines the main goals of the foreign policy activities of the Republic of Uzbekistan, analyzes the priority directions of foreign policy set out in the new development strategy of Uzbekistan for 2022-2026, identifies the specific features of the new foreign policy of Uzbekistan, and also draws theoretical conclusions on this issue.
Keywords: Foreign policy, main goals of foreign policy activities, Republic of Uzbekistan, priority areas of foreign policy, specific features of foreign policy.